2012
DOI: 10.1002/pmic.201200231
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth analysis of low abundant proteins in bovine colostrum using different fractionation techniques

Abstract: Bovine colostrum is well known for its large content of bioactive components and its importance for neonatal survival. Unfortunately, the colostrum proteome is complicated by a wide dynamic range, because of a few dominating proteins that hamper sensitivity and proteome coverage achieved on low abundant proteins. Moreover, the composition of colostrum is complex and the proteins are located within different physical fractions that make up the colostrum. To gain a more exhaustive picture of the bovine colostrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 62 publications
5
60
0
Order By: Relevance
“…Previous research identified milk proteins in bovine colostrum and mature milk (D'Alessandro et al, 2011;Nissen et al, 2012;Sacerdote et al, 2013), and the quantitative differences in the milk proteome between bovine colostrum and mature milk (Stelwagen et al, 2009;Zhang et al, 2015). So far, however, variation has not been studied in these low-abundant proteins in mature bovine milk over the whole lactation (from early to the end of lactation).…”
Section: Introductionmentioning
confidence: 94%
“…Previous research identified milk proteins in bovine colostrum and mature milk (D'Alessandro et al, 2011;Nissen et al, 2012;Sacerdote et al, 2013), and the quantitative differences in the milk proteome between bovine colostrum and mature milk (Stelwagen et al, 2009;Zhang et al, 2015). So far, however, variation has not been studied in these low-abundant proteins in mature bovine milk over the whole lactation (from early to the end of lactation).…”
Section: Introductionmentioning
confidence: 94%
“…Previously, we published 2 comprehensive proteomebased studies of the of the proteins present in bovine colostrum sampled from the first milking after calving and in milk sampled on d 10 (Nissen et al, 2012(Nissen et al, , 2013. These results allow us to investigate whether biologically active proteins other than immunoglobulins were exclusive to colostrum or present in higher concentrations in colostrum than in milk.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics has been used to characterize protein changes in the transition from colostrum to milk in cattle [16,17]. Additionally, the study of low abundance proteins from different body fluids such as blood plasma, colostrum or milk is becoming increasingly relevant [16,18-21].…”
Section: Introductionmentioning
confidence: 99%